The Impact Of Industry 4.0 On Human Resource Management - Hussain, Ali (جامعة الوادي University of Eloued, 2025)
This study explores the impact of Industry 4.0 on Human Resource Management (HRM), focusing on the transformation of HR practices into HRM 4.0. Industry 4.0, characterized by the integration of advanced technologies such as cyber-physical systems, the Internet of Things (IoT), and artificial intelligence, is reshaping workplace dynamics and labor requirements. The research highlights how Industry 4.0 is driving the digitalization of HR functions, leading to the emergence of HRM 4.0, which emphasizes efficiency, cost reduction, and strategic alignment with technological advancements. The study identifies key changes in HR processes, including recruitment, training, performance management, and compensation, while also addressing challenges such as workforce reduction, skill gaps, and resistance to change. The findings suggest that while Industry 4.0 offers significant benefits in terms of productivity and innovation, it also poses risks related to unemployment and the need for upskilling. The paper concludes with recommendations for HR managers to adapt to these changes by fostering a culture of continuous learning and leveraging digital tools to enhance organizational performance
The Impact of Industry 4.0 on Human Resource Management: Transitioning to HRM 4.0 in the Digital Era
Keywords: Industry 4.0; HRM 4.0; Digital Transformation; Workforce Automation; Human Resource Management